2012
DOI: 10.1080/13854046.2012.655781
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neuropsychological, Neuroanatomical, and Life Outcome in Hippocampal Amnesia

Abstract: Focal bilateral hippocampal damage typically causes severe and selective amnesia for new declarative information (facts and events), a cognitive deficit that greatly impacts the ability to live a normal, fully-independent life. We describe the case of 1846, a 48-year-old woman with profound hippocampal amnesia following status epilepticus and an associated anoxic episode at age 30. 1846 has undergone extensive neuropsychological testing on many occasions over the 18 years since her injury, and we present data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 114 publications
3
22
2
1
Order By: Relevance
“…Results indicated hippocampal volume reduction of 29.5% on the left and 31.2% on the right compared to controls, limited to the hippocampal formation and equally distributed across the subfields and the anterior-posterior axis, which is significantly lower than previous estimates of 48.1% on the left and 43.5% on the right based on averaged patient group volumes (Adlam et al, 2005). The finding of equivalent volume loss across hippocampal subfields in H.C. is inconsistent with reports of a selective vulnerability of the CA1 subfield to the effects of hypoxia (Kawasaki et al, 1990;Warren et al, 2012). Although abnormal orientation of the hippocampi, absence of the mammillary bodies, and other anatomical anomalies were also noted in H.C., the possibility of congenital maldevelopment and hypoplasia of limbic structures was not contemplated until the current study.…”
Section: Participantscontrasting
confidence: 69%
“…Results indicated hippocampal volume reduction of 29.5% on the left and 31.2% on the right compared to controls, limited to the hippocampal formation and equally distributed across the subfields and the anterior-posterior axis, which is significantly lower than previous estimates of 48.1% on the left and 43.5% on the right based on averaged patient group volumes (Adlam et al, 2005). The finding of equivalent volume loss across hippocampal subfields in H.C. is inconsistent with reports of a selective vulnerability of the CA1 subfield to the effects of hypoxia (Kawasaki et al, 1990;Warren et al, 2012). Although abnormal orientation of the hippocampi, absence of the mammillary bodies, and other anatomical anomalies were also noted in H.C., the possibility of congenital maldevelopment and hypoplasia of limbic structures was not contemplated until the current study.…”
Section: Participantscontrasting
confidence: 69%
“…In each case, and as described in more detail elsewhere (Buchanan et al, 2005; Allen et al, 2006; Hannula et al, 2006; Warren et al, 2012a,b; Watson et al, 2013), amnesia was secondary to an anoxic event and structural MRI scans, obtained from four patients, confirmed bilateral hippocampal volume reductions. Significant loss was also evident for a subset of these individuals in the parahippocampal gyrus, but these reductions were less extensive than corresponding volume changes in the hippocampus.…”
Section: Methodssupporting
confidence: 53%
“…Significant loss was also evident for a subset of these individuals in the parahippocampal gyrus, but these reductions were less extensive than corresponding volume changes in the hippocampus. A coronal MRI scan through the hippocampus for patient 1606, which shows hippocampal volume changes bilaterally can be seen in Bechara et al (1995), and high-resolution structural MRI scans for patient 1846 can been seen in Warren et al (2012b). The remaining patient (2563) is not eligible for MRI scanning, but visual inspection of CT scans suggests focal hippocampal damage.…”
Section: Methodsmentioning
confidence: 95%
“…A handful of recent investigations have implicated the hippocampus in online processing and comparison of complex materials like the scenes used here (Voss et al, 2011; Warren, et al, 2011, 2012; Yee et al, 2014b; see Lee et al, 2012 and Olsen et al, 2012 for reviews; but see Erez et al, 2013), and evaluation of our reaction time data indicates that patients were slower to respond than healthy comparison participants when test trials were administered 1 . This outcome may reflect slower detection of differences across scenes (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…Whether, and under what circumstances, the hippocampus contributes to short-term memory is currently a matter of debate (cf. Jeneson & Squire, 2011; Yonelinas, 2013), but converging evidence from neuroimaging (e.g., Axmacher et al, 2007; Davachi & Wagner, 2002; Hannula & Ranganath, 2008; Karlsgodt et al, 2005; Nichols et al, 2006; Piekema et al, 2006; Ranganath & D’Esposito, 2001; Schon et al, 2004; Stern et al, 2001) and neuropsychological (e.g., Cashdollar et al, 2009; Hartley et al, 2007; Olson et al, 2006; Warren et al, 2012; Watson et al, 2013; Yee et al, 2014a) studies is mounting in favor of this view. Consistent with these studies, we found that amnesic patients who participated in the current experiment were impaired on the memory tests used here even when there were no intervening items between corresponding study and test displays.…”
Section: Discussionmentioning
confidence: 99%